Reverberate, resonate, reproduce: a reconsideration of ideological influence in crime news production - Chagnon, Nick (Critical criminology, 2015)
For decades, scholars have increasingly been concerned with media representations of crime. Content analyses have chronicled pervasive distortions in media representations of crime. Many have argued these issues are particularly troubling in the news, as it supposedly provides an invaluable democratic service, spurring many theories of crime news production. Classic works often conceptualized crime news as either a product of dominant ideologies and top-down power, or journalistic routines and values, coupled with reflexive agency by journalists. More recently scholars have argued for hybrid perspectives. However, such hybridized approaches often brusquely treat the role of ideology in crime news. This article rethinks the role of ideology in crime news production, particularly the ways in which various ideologies interact and mutually strengthen each other.